Enhanced electrochemical properties of Al2O3-coated LiNiPO4 cathode materials for lithium-ion batteries - K. Rajammal; Arshid, Numan; Dhar Malingam, Sivakumar (Springer Science and Business Media Deutschland GmbH, 2024)
Cathode materials play a vital role in lithium-ion batteries to evaluate its performance. LiNiPO4 is one of the attractive cathodes due to its high voltage accompanied by olivine structure. The synthesis of LiNiPO4 cathode materials using an oxalic acid-assisted sol–gel method resulted in pristine samples, which were subsequently coated with 1 wt.% and 2 wt.% Al2O3 to investigate the impact on electrochemical properties. Structural analyses employing X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy revealed that the Al2O3-coated LiNiPO4 samples exhibited enhanced crystallinity and smaller crystallite sizes compared to the pristine material. The initial discharge capacities were measured at 119.05 and 115.48 mAhg−1 for the 1 and 2 wt.% Al2O3-coated samples, respectively, slightly higher than the pristine sample’s discharge capacity of 110.71 mAhg−1. During cycling, the Al2O3-coated samples initially demonstrated superior capacity retention and cycling performance. Specifically, the 1 wt.% Al2O3-coated sample maintained good capacity retention throughout the cycles, indicating improved lithium-ion diffusion and structural stability. In conclusion, the study highlights that an optimal amount of Al2O3 coating enhances the structural properties and lithium-ion diffusion within LiNiPO4 cathode materials, significantly improving their electrochemical performance. The findings underscore the importance of controlled coating strategies in optimizing the functionality and longevity of battery materials for advanced energy storage applications.